The Effect of Customer Trust and Service Quality on Online Transportation Consumer Satisfaction on Stiami Institute Students - Siti Aisah; Resista Vikaliana; Eman Sulaeman Nasim (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of customer trust and service quality on consumer satisfaction of online grab transportation among students of the Stiami Institute. The population in this study were some students of the Stiami Institute with a total sample of 145 respondents who were selected using the accidental sampling technique. Data was collected through questionnaires in which each respondent was given 29 questions. Based on hypothesis testing using t-test, it is known that customer trust and service quality have a significant effect on customer satisfaction. Based on the results of the f test, it is known that all the independent variables in this study have a significant effect on consumer satisfaction. R Square value of 0